Two Propagation Pathways of the Boreal Summer Quasi-Biweekly Oscillation of the Atmospheric Heat Source Over the Tibetan Plateau. Issue 1 (1st January 2020) - Zhong, Shanshan; Jia, Qiao; Zhu, Zhiwei; Zhang, Xinchang
ABSTRACT: Based on the daily Japanese 55-year Reanalysis data, the characteristics of the summer (June–July–August) quasi-biweekly oscillation (QBWO) of atmospheric apparent heat sources over the Tibetan Plateau (TP) and its surrounding areas (TPSR) are investigated. The first three leading modes of the atmospheric intraseasonal heat source over the TPSR reflect two independent propagation features of the QBWO. The first, which propagates from east to west, is associated with the mid- to upper tropospheric circulation, with large-scale anomalous cyclones and anticyclones propagating from northeast China, across the TP, and finally arriving in West Asia. The intensity of this QBWO rapidly increases when approaching the TP and significantly weakens during its westward journey upon leaving the TP. The second, which moves from west to east, is closely correlated with the mid-latitude Rossby wave train emanating from southern Europe that travels over the TP to the East Asian coast. Remarkable differences can be observed between the intensity of the wave train over the east and west sides of the TP. To the west of 90°E, the QBWO strengthens when proceeding to the TP and reaches its maximum over the TP. To the east of 90°E, the circulation anomalies are maintained for about half a cycle. For both propagation pathways, the QBWO of the heat source over the TPSR greatly modulates the circulation and precipitation anomalies over the TP, the Indian Peninsula, and the Indochina Peninsula.